Kompetensi Pedagogis Guru PAI dalam Pengelolaan Kelas di MI Ma’arif Purwodeso Kecamatan Sruweng Kabupaten Kebumen - Maulida, Marwah Ana Nur; Rinawati, Atim (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
This research aims to determine the pedagogical competence of Islamic Education Teachers in the learning process and to determine the mechanisms of Islamic Education Teachers in managing classes at MI Ma'arif Purwodeso. The subjects in this research were PAI teachers at MI Ma'arif Purwodeso, Sruweng District, Kebumen Regency. Meanwhile, the object is the teacher's pedagogical competence in the PAI learning process at MI Ma'arif Purwodeso, Sruweng District, Kebumen Regency. The data collection techniques used were observation, interviews and documentation. Based on the results of the research that has been carried out, the author can draw conclusions, namely: The Pedagogical Competence of PAI Teachers at MI Ma'arif Purwodeso Sruweng Kebumen in providing understanding to students is carried out through several stages, namely Curriculum/Syllabus Development, Learning Planning and Implementation, Preparation of Learning Programs, Implementation of Learning, Evaluation of Learning Results and Student Development. Apart from that, the mechanism for the Islamic education learning process at MI Ma'arif Purwodeso is carried out by teachers managing the class effectively without dominating or being busy with their own activities so that all students' time can be utilized productively, Monitoring Activities (What it looks like when delivering learning), Modifying Student Behavior, Emphasis on Positive Things and Cultivating Self-Discipline